Effect of a tight necktie on intraocular pressure. Issue 8 (24th July 2003) - Teng, C; Gurses-Ozden, R; Liebmann, J M; Tello, C; Ritch, R
Abstract : Aim: To evaluate the effect of a tight necktie on intraocular pressure (IOP) measurement using Goldmann applanation tonometry. Methods: 40 eyes of 20 normal subjects and 20 open angle glaucoma patients (all male) were enrolled. IOP was measured with an open shirt collar, 3 minutes after placing a tight necktie, and 3 minutes after loosening it. All measurements were made by the same examiner. Results: Mean IOP in normal subjects increased by 2.6 (SD 3.9) mm Hg (p=0.008, paired t test; range −3 to +14 mm Hg) and in glaucoma patients by 1.0 (1.8) mm Hg (p=0.02, paired t test; range −2 to +4.5 mm Hg). In normal subjects, IOP in 12 eyes was increased by ⩾2 mm Hg and in seven eyes by ⩾4 mm Hg. In glaucoma patients, IOP in six eyes was increased by ⩾2 mm Hg and in two eyes by ⩾4 mm Hg. Conclusion: A tight necktie increases IOP in both normal subjects and glaucoma patients and could affect the diagnosis and management of glaucoma.